Test of Antioxidant And Antibacterial Activity of Ethanol Extract of Andaliman Fruit (Zanthoxylum Acanthopodium Dc.) With Dpph (1.1-Diphenyl-2-Picrylhydrazil) Trapping Method And Minimum Inhibitory Concentration - Ira Syaputri; Ermi Girsang; Linda Chiuman (CV. Inara, 2022)
Utilization of bioavailability according to World Health Organization (WHO) records is very large, it is estimated that almost 80% of mankind, especially in developing countries, still use plants as medicinal ingredients to maintain their health (Nugraheni, 2007). Andaliman (Zanthoxylum acanthopodium DC.) which belongs to the Rutaceae tribe which is one of the plants known to the Batak community, is classified as a wild plant and is a typical plant of Province North Sumatra. The method used in this research is experimental research. The research included collecting and processing andaliman fruit, making simplicia, making ethanol extracts, and examining antioxidant activity tests using the DPPH free radical scavenging method (1,1-diphenyl-2-picrylhydrazil) and antibacterial activity using the minimum inhibitory concentration method. The results of the antibacterial activity test of the ethanolic extract of andaliman fruit showed that the extract had antibacterial activity in the moderate category at a concentration of 300 mg/ml with an inhibition zone of 10.17 mm for Staphylococcus aureus bacteria and a moderate category for Staphylococcus epidermidis bacteria with an inhibition zone of 10.80 mm. The ethanol extract of andaliman fruit can inhibit Staphylococcus aureus and Staphylococcus epidermidis, effective at a concentration of 300 mg/ml with inhibitory diameters of 10.17 mm and 10.80 mm, respectively.